Polymeric Membrane Sensors for Detection of Cesium (I), Chromium (III) and Titanium (III) Ions Based on Calixarene Ionophores - Ahmadzadeh, Saeid (2011)
Ion selective electrodes (ISEs) allow the potentiometric sensing of the activity of specific ions in the presence of other ions in aqueous and non-aqueous solutions. ISEs are invaluable tools for continuous monitoring and can be used in environmental, agricultural, industrial and clinical fields. They measure the activity rather than the concentration and are not affected by turbidity or sample color. In order to obtain highly selective polymeric membrane ISEs, suitable ionophores must be doped into the fabricated PVC membranes. Ionophores used namely p-Isopropylcalix[6]arene (L1), 4-Isopropylcalix[4]arene (L2) and meso-octamethylcalix[4]pyrrole (L3) are group of calixarenes that is bowel shaped super molecular compounds which can bind selectively to the target ion and act as an ion carrier in the membrane. Three novel high selective membrane sensors were fabricated for selective and sensitive determination of trace amount of three very significant cations, cesium (I), chromium (III) and titanium (III) using (L1), (L2) and (L3) as the ion sensing reagents, respectively. A novel cesium selective membrane electrode based on p-Isopropylcalix[6]arene as an ionophore was fabricated. The amounts of ionophore (5 mg), PVC (30 mg), dioctyl phthalate (DOP) as a plasticizer (62 mg) and potassium tetrakis (4-chloro-phenyl)borate (KTpClPB) as a lipophilic additive (3mg) were optimized in the preparation of the membrane. The sensors exhibited significantly enhanced response towards cesium ions over the concentration range of 1.0×10